Kepuasan Kerja sebagai Mediator antara Pengembangan Karier, Dukungan Atasan, dan Organizational Citizenship Behavior - Tri Kusuma, Nala (Journal of Indonesian Economic Research, 2025)
This study aims to examine the mediating role of job satisfaction on career development and supervisor support towards organisational citizenship behaviour. The sampling technique used was random sampling. This study found that perceived supervisor support and career development have a significant positive effect on job satisfaction, perceived supervisor support and career development have a significant positive effect on organisational citizenship behaviour, and job satisfaction has a significant positive effect on organisational citizenship behaviour. The results show that job satisfaction acts as a mediator in the relationship between career development and organisational citizenship behaviour. The results also show that job satisfaction acts as a mediator in the relationship between perceived supervisor support and organisational citizenship behaviour. The implications of this study provide an overview for organisations to make strategic decisions in improving career development programmes and strengthening support for employees in the workplace.